Beirando a vida, driblando os problemas: estratégias de bem viver - Gadelha, Maria Jacqueline Abrantes (2007)
The purpose of this study is to analyze the strategies used by families living in at-risk-and-vulnerable situations registered with the Estratégia Saúde da Família (ESF) ( Family Health Strategy ) as they face their daily problems. This is an investigation of a qualitative nature, using interview as the main tool for an empirical approach. Ten women from the Panatis location in northern Natal, Rio Grande do Norte, whose families live in precarious social-economical situations were interviewed. The interviews occurred between the months of April and June, 2007. The reports revealed that a mixture of improvisations and creativity was used as strategies for overcoming the privations and necessities of daily life. We also reached the conclusion that these families sought solutions for their problems through religiosity and a gift reciprocity system as resources for obtaining personal recognition and support in adversity. The results, in addition, point to ESF as one of the strategies used by these families in the search for attention and care. From this perspective, ESF has proven to be a place for listening and the construction of ties that are consolidated through home visits, organized groups, in parties and outings that are promoted in the community, reestablishing contact and support among people and signaling a way out of abandonment and isolation. Holders of knowledge constructed through life experiences, the participants of the study led us to induce and infer the need to amplify space that will allow them to express meanings, values and experiences, and consider that becoming ill is a process that incorporates dimensions of life that go beyond the physical. As health professionals, we need to be aware of the multiple and creative abilities used in the daily lives of these families, so that we can, along with them, reinvent a new way of dealing with health